(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Totally 80 disk-shaped specimens of Filtek™ Bulk-Fill, 3M ESPE, and Filtek™ Z250 XT, 3M ESPE, were prepared by using split-Teflon mold (4mm×10mm). Specimen characterization XRD, Surface roughness, degree of conversion, Surface microhardness, and depth of cure of the specimens were evaluated after the specimens were stored in distilled water in darkness at 37°C for 24 h. Statistical analysis was done using t-test with a significance level at p<0.05. FiltekTM Z350 XT showed the highest mean value of Vickers microhardness either on top surface 94.94% or bottom surface 69.92% and recorded 76.51% while FiltekTM Bulk-Fill was 66.85% for depth of cure. Filtek bulk-fill recorded a lower mean value of 0.73 for Surface roughness than FiltekTM Z350 XT and the highest degree of conversion of 84.34%. Statistical analysis showed that there was a significant difference between the mean values for all tested results. Increasing the filler content proved to have ability to enhance some properties, specially the surface roughness. Incorporation of some structurally rigid monomers like Bis-DMA, UDMA, TEGDMA within the resin matrix have a great influence on the measured properties, including degree of conversion reached to 84.34%, depth of cure to a level of 76.51% and Vickers microhardness to 94.94%.